Molecular Characterization of the Bacterial Community in Biofilms for Degradation of Poly(3-Hydroxybutyrate-co-3-Hydroxyhexanoate) Films in Seawater - Morohoshi, Tomohiro (Microbes Environ, 2018)
Microplastics are fragmented pieces of plastic in marine environments, and have become a serious environmental issue. However, the dynamics of the biodegradation of plastic in marine environments have not yet been elucidated in detail. Polyhydroxyalkanoates (PHAs) are biodegradable polymers that are synthesized by a wide range of microorganisms. One of the PHA derivatives, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) has flexible material properties and a low melting temperature. After an incubation in seawater samples, a significant amount of biofilms were observed on the surfaces of PHBH films, and some PHBH films were mostly or partially degraded. In the biofilms that formed on the surfaces of unbroken PHBH films, the most dominant operational taxonomic units (OTUs) showed high similarity with the genus Glaciecola in the family Alteromonadaceae. On the other hand, the dominant OTUs in the biofilms that formed on the surfaces of broken PHBH films were assigned to the families Rhodobacteraceae, Rhodospirillaceae, and Oceanospirillaceae, and the genus Glaciecola mostly disappeared. The bacterial community in the biofilms on PHBH films was assumed to have dynamically changed according to the progression of degradation. Approximately 50 colonies were isolated from the biofilm samples that formed on the PHBH films and their PHBH-degrading activities were assessed. Two out of three PHBH-degrading isolates showed high similarities to Glaciecola lipolytica and Aestuariibacter halophilus in the family Alteromonadaceae. These results suggest that bacterial strains belonging to the family Alteromonadaceae function as the principal PHBH-degrading bacteria in these biofilms.